2023
DOI: 10.3389/fneur.2023.1161527
|View full text |Cite
|
Sign up to set email alerts
|

Impact of sex and APOE-ε4 genotype on patterns of regional brain atrophy in Alzheimer's disease and healthy aging

Abstract: Alzheimer's Disease (AD) is a heterogeneous disease that disproportionately affects women and people with the APOE-ε4 susceptibility gene. We aim to describe the not-well-understood influence of both risk factors on the dynamics of brain atrophy in AD and healthy aging. Regional cortical thinning and brain atrophy were modeled over time using non-linear mixed-effect models and the FreeSurfer software with t1-MRI scans from the Alzheimer's Disease Neuroimaging Initiative (N = 1,502 subjects, 6,728 images in tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 94 publications
0
3
0
Order By: Relevance
“…We replicated previous literature indicating that the APOE ε4-allele has a significant negative impact on cognition. In exploratory analyses, we compared the impact of the APOE ε4-allele in autistic male and NT males and females on verbal learning, since previous studies suggest that sex/gender influence ASD, Alz, and the effect of APOE, respectfully [31][32][33][34]. We put forward new findings showing that only autistic male APOE ε4 carriers had a worse performance in verbal learning abilities, while this was not the case for NT males or females.…”
Section: Discussionmentioning
confidence: 99%
“…We replicated previous literature indicating that the APOE ε4-allele has a significant negative impact on cognition. In exploratory analyses, we compared the impact of the APOE ε4-allele in autistic male and NT males and females on verbal learning, since previous studies suggest that sex/gender influence ASD, Alz, and the effect of APOE, respectfully [31][32][33][34]. We put forward new findings showing that only autistic male APOE ε4 carriers had a worse performance in verbal learning abilities, while this was not the case for NT males or females.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been observed that this pathology affects women more than men, with higher levels of neuroinflammatory, neurotrophic and serotoninergic markers found in women, and a stronger relationship between neuroinflammatory and neurotrophic factors, together with the severity of depressive symptoms, in this sex [21,[157][158][159][160].…”
Section: Depressionmentioning
confidence: 97%
“…Although AD may affect females with more intensity, more rapid brain atrophy, and faster cognitive decline than in males, it does not appear to do so earlier (53,54). The higher prevalence of AD in females is mostly driven by a divergence of prevalence rates in males and females with increasing age (55,56).…”
Section: Hyperfunctional Glia In Female Apoeɛ4 Noncarriersmentioning
confidence: 99%